Evaluation and development of urban tourism with a sustainable development approach (Case study: District Ain Al-Tamur of Kerbala) - Moslim Ali Obieas Al- Shamari (Peerian Journals Publishing, 2022)
The management and development of urban tourism is a balancing weight to achieve sustainable urban tourism. Any type of inefficiency in the management of urban tourism has many negative consequences due to the complexity of the tourism flow in today's era. In this regard, a special attitude towards urban tourism can be considered one of the most important factors of sustainable urban development. For this purpose, today, in addition to observing the growth of scientific studies and research, we are witnessing a change in the attitude of many city managers in this direction, so leafy cities such as Kerbala have also benefited from this issue. This research is analytical-descriptive in nature and has an applied purpose. Therefore, the importance of investigating the development of urban tourism has become one of the most profitable and important types of tourism. Since the Ain Al-Tamur region as a region with diverse tourist attractions, the presence of important economic centers and specialized markets with extra-regional and extra-urban functions as the main pillar of the region's economy has led to the concentration of commercial activities. Accordingly, a large number of visitors come to this area every day, so proper planning in the field of creating a suitable tourism environment in the area can help the sustainable development of this area. In this regard, the SWOT model has been used to analyze the current research. Based on the obtained results, the performance in the field of tourism in the region is weak and faces many extra-systemic challenges. Based on the obtained results, solutions and suggestions were presented in the field of the formation of centralized tourism management in the region
Keywords: urban tourism development; SWOT; sustainable development